Pale moon - Glick, Jesse G. M., 1874-1938 (Lyricist); Logan, Frederic Knight, 1871-1928 (Composer) (Sims Song Slide Corporation (Kirksville, Mo.), 1920)
Songs; Scores; Glass lantern slide depicting score of "Pale Moon."